Die Bedeutung der Allgemeinen Gleichgewichtstheorie für die Transformation zentral geplanter Ökonomien - Hahn, Frank (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1994)
In this paper the relevance of General Equilibrium Theory for the understanding of the Eastern European transformations is discussed. Using several examples and problems it is demonstrated that GET illuminates the classical problem of Adam Smith: how market coordination is possible without central controll. However, because of its formal mode of construction and the non-empirical character of its basic assumptions the theory cannot have any descriptive relevance. Contrary to the claims of most main-stream economists, it is argued that the transformation should aim for a mixed economy in which the state has to take an important task, which either could not be solved by markets or for which markets do not exist.